2018
DOI: 10.1111/gcb.14166
|View full text |Cite
|
Sign up to set email alerts
|

Temperature influences habitat preference of coral reef fishes: Will generalists become more specialised in a warming ocean?

Abstract: Climate change is expected to pose a significant risk to species that exhibit strong behavioural preferences for specific habitat types, with generalist species assumed to be less vulnerable. In this study, we conducted habitat choice experiments to determine how water temperature influences habitat preference for three common species of coral reef damselfish (Pomacentridae) that differ in their levels of habitat specialisation. The lemon damselfish Pomacentrus moluccensis, a habitat specialist, consistently s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 107 publications
(153 reference statements)
0
12
0
Order By: Relevance
“…By definition, generalist species can cope with wider ranges of environmental conditions than specialists (Gilchrist, 1995), so our finding that the potential for establishment into new habitats is greater for the more flexible species is not surprising. However, the condition of generalism can be ascribed to a hypervolume of traits, each of which can differ in importance depending on a particular set of biotic and abiotic circumstances (Betzholtz, Pettersson, Ryrholm, & Franzén, 2013; Gilchrist, 1995; Kingsbury et al., 2019; Matis, Donelson, Bush, Fox, & Booth, 2018). Our models identified which traits and ecological mechanisms (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…By definition, generalist species can cope with wider ranges of environmental conditions than specialists (Gilchrist, 1995), so our finding that the potential for establishment into new habitats is greater for the more flexible species is not surprising. However, the condition of generalism can be ascribed to a hypervolume of traits, each of which can differ in importance depending on a particular set of biotic and abiotic circumstances (Betzholtz, Pettersson, Ryrholm, & Franzén, 2013; Gilchrist, 1995; Kingsbury et al., 2019; Matis, Donelson, Bush, Fox, & Booth, 2018). Our models identified which traits and ecological mechanisms (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the behaviours and patterns presented here may not be the same for A. vaigiensis within its native range. Matis () demonstrated that vagrant Scissor tale surgeon Abudefduf sexfasciatus (Lacepede 1801), a congener of A. vaigiensis , formed mixed‐species groups when occurring as a vagrant in temperate south‐eastern Australia but only formed single‐species groups within its native tropical range. The author attributes these results to the behavioural plasticity of tropical fishes exposed to novel temperate environments.…”
Section: Discussionmentioning
confidence: 99%
“… Richardson et al , 2018 , Roberts and Ormond, 1987 ) or changing temperatures (e.g. Donelson et al , 2010 , Habary et al , 2017 ) on reef fishes, few, if any, have considered how habitat availability may affect temperature choice and vice versa (see Matis et al , 2018 for exception). Understanding the nature and magnitude of the costs and benefits of associating with different habitat/s and thermal environments is crucial to predict how populations and distributions of coral reef fishes will respond to future conditions under ongoing ocean warming.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the lack of suitable habitat has been suggested to constrain the poleward expansion of some reef fish species ( Feary et al , 2014 , Munday et al , 2008b ). The only other study we are aware of that investigated the effects of temperature on habitat choice of coral reef fishes suggested that exposure to 22, 28 or 31°C influenced habitat selectivity of three species of juvenile damselfishes, and although some differences were reported, the effect sizes were small ( Matis et al , 2018 ).…”
Section: Discussionmentioning
confidence: 99%